From dignity to disgrace : a comparative analysis of Psalms 8 and 14 - Lioy, Dan T. (Conspectus : The Journal of the South African Theological Seminary, 2013)
This essay undertakes a comparative analysis of Psalms 8 and 14. Together, these hymns reveal that the Creator originally bestowed unparalleled dignity on human beings; yet, in their folly, the reprobates chose the path of indignity by rejecting God's existence and their ultimate accountability to their Creator. Moreover, an examination of both these poems discloses that in a future day, the Lord will judge the wicked and vindicate the upright. Put another way, while condemnation and doom are the fate of evildoers, eternal glory and honour are the destiny of the righteous.
free